ANTIHYPERGLYCEMIC THERAPY FOR PATIENTS WITH DIABETES MELLITUS TYPE 2 - Tomina, Е. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article describes the main classes of oral antihyperglycemic drugs, the mechanism of action, administration details, indications and contraindications. The innovative incretin-directed therapy was also covered. Rational algorithms of patients’ treatment with diabetes mellitus type 2 were presented.